Implementasi Merdeka Belajar Pendidikan Agama Islam di Tingkat Sekolah Dasar/Madrasah Ibtidaiyah Dengan Memanfaatkan Teknologi Informasi - Masruroh, Siti; Haerudin, Haerudin; Priyatna, Bayu (Jurnal Ilmiah Pengabdian Kepada Masyarakat (Nyiur-Dimas), 2023)
The purpose of study program-based community service is as an effort by lecturers to carry out the tridarma of higher education. In this case the Directorate General of Islamic Higher Religious Education (Diktis) provides a national level grant program for all lecturers under the ministry of religion. On this occasion, we propose a service with the theme Implementation of Freedom to Learn Islamic Religious Education at the Elementary School/Madrasah Ibtidaiyah Level by utilizing Information Technology, namely making an application "Islamic Smart Learning" for Madrasah Ibtidaiyah Al I'anah Dusun Kalihurip Duren Village, Klari District, Karawang Regency. This service activity is a contribution of the PAI Study Program to the world of elementary/Madrasah Ibtidaiyah education as a means of utilizing information technology in the independent learning program with the principle of independent learning, it is assumed that students are given freedom to access learning media that is more intelligent and enjoyable. So that the learning potential of students will grow more measurably and directed because there are more interactive learning media.